The Impact of Physical Activity on Skin Health and Skin Aging - Hetnar, Paulina; Fortuna, Milena; Kiper, Sebastian; Toczek, Sławomir; Tomala, Magdalena; Jastrowicz-Chęć, Katarzyna; Koryszko, Klaudia; Pokrywka, Natalia; Suwała, Dawid; Polak, Marcelina (Quality in Sport, 2025)
Purpose: The aim of this review is to synthesize current literature regarding skin structure and function, the mechanisms of intrinsic and extrinsic aging, and the potential benefits of physical activity for general health, as well as its specific effects on skin aging. Materials and research methods: The article is based on an analysis of research available on PubMed and Google Scholar. A literature review was conducted using following keywords such as “skin aging”, “skin health”, “intrinsic aging”, “extrinsic aging”, “physical activity”, “health”, “exercise”, and “the impact of physical activity on health”. Results: Skin aging results from both intrinsic factors such as genomic instability, epigenetics, telomere shortening, and mitochondrial dysfunction, and extrinsic factors including UV radiation, pollution, smoking, and poor lifestyle habits. Regular physical activity supports skin health by enhancing circulation, promoting collagen synthesis, reducing oxidative damage, modulating hormones, and improving mitochondrial function. Exercise also indirectly benefits the skin by supporting overall health and reducing lifestyle-related risk factors. Conclusion: Physical activity is a promising non-pharmacological strategy for preserving skin integrity and slowing age-related changes. Its incorporation into preventive dermatological care may complement conventional treatments and promote healthy aging. However, further investigations are required to elucidate the underlying mechanisms by which exercise influences the skin aging process.